2020
DOI: 10.1177/0260106019900731
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary protein intake on factors associated with male infertility: A systematic literature review and meta-analysis of animal clinical trials in rats

Abstract: Background: Studies have shown that the amount of protein in the diet affects the hypothalamic-pituitary-testis axis and sub-optimal quantity reduces male fertility potential in both animals and humans. However, individual research reports on the factors associated with male infertility are collectively uncharacterized. Aim: We systematically reviewed, and meta-analysed animal (rats) studies on the effect of low protein diet on factors associated with male infertility. Methods: PubMed Central, EMBASE and Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
(56 reference statements)
3
10
0
Order By: Relevance
“…It is known that nutrition has an effect on FSH and LH levels [27]. Ajuogu and coauthors [28] has reported that low protein diet caused significant reductions in serum FSH concentration in rats. Similarly, in a previous study by Polkowska and coauthors [29] has raported that the low protein diet influenced the exerted an inhibitory effect on the synthesis and the release of LH in the pituitary gonadotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that nutrition has an effect on FSH and LH levels [27]. Ajuogu and coauthors [28] has reported that low protein diet caused significant reductions in serum FSH concentration in rats. Similarly, in a previous study by Polkowska and coauthors [29] has raported that the low protein diet influenced the exerted an inhibitory effect on the synthesis and the release of LH in the pituitary gonadotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins are not energetic substrates for sperm cells [ 32 , 33 ]; moreover, a high-protein diet had no significant effect on glycemic control [ 83 ]. However, a low-protein diet has been considered a potential risk factor for male-factor infertility, causing a significant reduction in testis, epididymis, and seminal vesicle weights, as well as a decrease in serum testosterone [ 84 ]. Conversely, the reports on the effect of a high-protein diet present in the literature are contradictory [ 85 ].…”
Section: Nutrients Impacts On Molecular Aspects Related To Sperm Qualitymentioning
confidence: 99%
“…During the critical physiological state (pregnancy), most women run unconsciously into a state of undernutrition with unknown consequences in subsequent generations. Studies have shown that sub-optimal protein consumption reduces the gonadal and endocrine function, and consequently male infertility [9], but little is known about exposure at intrauterinecondition, and if persistence of this malnutrition could cause the same deleterious effects or there is an adaptive shift in response. With focus on the male reproductive function in adolescents of first-and second-generation following exposure to protein deficient status, this study aimed to assess effects of protein deficiency on sperm quality parameters.…”
Section: Semen Analysis and Morphological Study Of Two Subsequent Genmentioning
confidence: 99%